An investigation of the psychometric properties of the strong brand questionnaire in sport - Habib Honarı; Mehrzad Hamıdı; Fatemeh Kıanı; Mona Rezaeı (Türk Spor ve Egzersiz Dergisi)
Making strong brands has become a priority for many organizations in marketing. Brand is an important indicator of marketing status. Brand strength is in kept customer, profit, brand development and gain competitive advantage and In fact it is a concept that was created from a consumer perspective. It is assumed that the creation of a strong brand is creating numerous marketing benefits. The purpose of this study was to evaluate the psychometric characteristics of the questionnaire the most strong sports brands in the consumer society. Questionnaire was conducted to a sample of 340 customers of sports brands. Psychometric parameters were determined by using appropriate statistical methods. The results of the factor analysis and Varimax rotation revealed five factors of strong brands. The results confirms that questionnaire structure have acceptable associated to the data and confirmed all indicators of the model. Reliability (859/0) was satisfactory. According to calculated psychometric indices, this questionnaire could be appropriate to assess the most strong sports brands.